Environmental Uncertainty: Typology Of Strategy And Strategic Management Accounting Techniques On Company Performance - Marten PUYO; Sutrisno T; Aulia Fuad RAHMAN; Erwin SARASWATI (Indonesia Strategic Sustainability, 2022)
Uncertain environmental conditions and typology of corporate strategy are the determining factors in improving company performance. This study aims to prove the analysis results of the typology of strategic management accounting techniques on company performance and test the role of environmental uncertainty in moderating the typology of strategies on company performance. This research is quantitative research with data collection using a survey method. The sample in this study was 237 managers of manufacturing companies listed on the Indonesia Stock Exchange (IDX). Sampling using the type of probability sampling. Data analysis in this study used the PLS-SEM (partial least square modeling) analysis method through the SmartPLS 3.0 program. There are three findings in this study, namely. First, the typology of strategy has a significant effect on company performance. Second, strategic management accounting techniques have a substantial impact on company performance. Third, environmental uncertainty has strengthened the influence of strategy typology on company performance. This study also analyzes the results of the 'Fit' contingency test for the prospector, defender, and analyzer strategy typology variables on company performance through crosstab analysis using the SPSS.25 program. Based on the results of the contingency fittest, it has been proven that when conditions of environmental uncertainty are high in a competitive environment, companies can use a strategy typology with a prospector strategy rather than a company with a defender or analyzer strategy. The fittest prospector strategy typology is more appropriate for companies to improve performance.